Understanding the legacy of dependency and powerlessness experienced by farm workers on wine farms in the Western Cape - Falletisch, Leila Ann (Stellenbosch : University of Stellenbosch, 2008)
Thesis (M Social Work (Social Work))--University of Stellenbosch, 2008.